Financial analysis fundament for assessment the value of the company - Goran Karanovic; Sinisa Bogdan; Suzana Baresa (UTMS Journal of Economics, 2010)
Lack of capital market development cause that calculating the value of companies in the small markets, such as the Croatian market, is carried out primarily from the analysis of financial statements. Lack of market development is evident from the unrealistic and unobjective corporate values, as result of too small volume of securities trading in financial markets. The primary financial analysis is the basic method for estimating company value, and represents the foundation for an objective determination of cash flow components that will be discounted. Trought analysis investors are trying to answer the questions such as: status of the assets, liabilities and capital, the dynamics of business enterprises, the level of solvency and liquidity, utilization of fixed assets, contribution of fixed assets in total income, company profitability rates and investment in the company. Investors use financial analysis only as a basis and as a tool to predict the potential for creating new business value.
Keywords: 330; financial analysis; horizontal analysis; vertical analysis; financial ratios; evaluation of company